Effect of Net‐Gun Capture on Survival of Mule Deer. Issue 4 (19th February 2020) - Van de Kerk, Madelon; McMillan, Brock R.; Hersey, Kent R.; Roug, Annette; Larsen, Randy T.
ABSTRACT: Capture techniques to deploy radio‐collars often risk mortality and injury to the animal. Capture‐induced mortality can affect population sizes but also introduces bias in survival estimates based on data from captured animals. In recent years, a large‐scale research and monitoring project in Utah, USA, has involved capturing and radio‐collaring hundreds of mule deer ( Odocoileus hemionus ), a species of great interest in large parts of North America. Our objective was to investigate how the survival rates of these mule deer were affected by capture and handling. During winters of 2014–2018, an experienced capture crew net‐gunned and fitted 1, 805 animals with global positioning system (GPS)‐collars. We estimated survival rates during the first 6 weeks after capture using Cox proportional hazard regression, and compared the survival rates of animals that were captured in a particular year to those of animals that were not captured but fitted with a GPS‐collar in a previous year. We used a model selection framework to evaluate how long survival rates of captured animals were different from those of animals that were not captured. Our results indicated that weekly survival rates of captured animals were 0.985 ± 0.003 (SE), 0.988 ± 0.002, and 0.990 ± 0.001 in weeks 1, 2 and 3, respectively. Weekly survival rates of captured deer during weeks 4–6 were 0.993 ± 0.001, the same as those of deer that were not captured at the same time. Furthermore, post‐capture survival rates were positively influenced by body size and negatively influenced by age. We conclude that the mortality resulting from helicopter capture was low but recommend comparing newly captured and previously captured individuals to examine what proportion of observed mortality is likely capture‐related. © 2020 The Wildlife Society. Abstract : Captured deer had higher mortality rates than non‐captured deer for 3 weeks following capture and survival rates of captured deer were negatively affected by age and positively affected by body mass. We recommend either spreading capture efforts over multiple years, so that it is possible to make comparisons between newly captured and previously captured individuals and examine what proportion of observed mortality is likely capture‐related, or excluding the initial 3 weeks after capture from analysis entirely.